Synthesis and Optoelectronic Characterization of Silicate Lattice-Based M3La2Si3O12 (M = Mg2+, Ca2+, Sr2+ and Ba2+) Nanophosphors for Display Applications. Issue 1 (2nd January 2020) - Sheoran, Suman; Singh, Sitender; Tanwar, Vijeta; Mann, Ajay; Singh, Vachan; Mari, Bernabe; Singh, Devender
Abstract : Eu 3+ doped M3 La2 Si3 O12 (M = Mg 2+, Ca 2+, Sr 2+, Ba 2+ ) materials were prepared using sol-gel technique. The samples were prepared at a temperature of 950 o C using 0.01-0.05 mole of Eu 3+ ion to examine worth of amount of activator ion on luminous intensity. Photoluminescence characteristics of these Eu 3+ incorporated inorganic fluorescent materials were explored using photoluminescence (PL) emission spectroscopy for display devices. These phosphor materials showed stable colour coordinates and their luminescence intensity enhanced with temperature. Upon 393 nm excitation, Eu(III) incorporated fluorescent materials exhibited intense red emission with high colour purity including three peaks at 589, 613-615 (dominant) and 650-655 nm corresponding to 5 D0 → 7 F1-3 transition. The structural parameters were determined using powder X-ray diffraction (PXRD) and transmission electron microscopy (TEM) techniques. The presence of sharp and intense peaks in the diffraction patterns confirmed high crystalline nature of the prepared materials that improved with increasing temperature. TEM images showed spherical particles with 13-36 nm size. Fourier transform infrared study was employed to determine the stretching frequencies of silicate groups and metal available in the prepared materials. The strong PL response and high chemical stability of Eu 3+ doped M3 La2 Si3 O12 phosphors made them suitable materials for applications in the full-colour displays and white light emitting diodes (WLEDs). GRAPHICAL ABSTRACT: